PERAN PEMBELAJARAN GEOGRAFI DALAM PEMBENTUKAN PENGETAHUAN DAN SIKAP PELESATARIAN LINGKUNGAN HIDUP PADA SISWA SMA - Alfian Novrizal (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractGeography learning about environmental preservation contains material about the understanding of environmental preservation, the importance of environmental preservation to the attitudes and efforts that are included in environmental conservation. The purpose of this study is to identify the knowledge and attitudes of environmental preservation to students and test how much the role of geography learning in shaping knowledge and attitudes towards environmental preservation in students. The study used the method of multiple regression analysis. The results showed that geography learning in school policy variables, teacher creativity, and learning material had a significant influence on the formation of knowledge about environmental preservation while the principal leadership variable did not have a significant influence on the formation of knowledge about environmental preservation. On the aspect of attitude, only the variable of teacher creativity has a significant influence on the formation of environmental preservation attitudes in students. Keywords: high school students, knowledge and attitude, role of geography learning